Shāh Esmā'il and his Three Wives : A Persian-Turkish Tale as Performed by the Bards of Khorasan - Youssefzadeh, Ameneh (Studies on Performing Arts & Literature of the Islamicate World, 2021)
This book is the first full text and translation of a prosimetric tale from the rich repertoire of Central and West Asian bards to be published with ready access to recordings of both the prose narration and the sung verse. In Iranian Khorasan, bards known as bakhshi present tales that in other regions are performed wholly in a Turkic language with prose narration in Persian, Khorasani Turkish or Kurmanji Kurdish and most verses in Turkish. We compare portions of the full performance transcribed here with excerpts from two performances of Iranian bakhshis in the 1970s. Three introductory chapters and a commentary discuss musical and verbal dimensions of the bakhshi's art in relation to relevant social, historical, and literary contexts.